Variation of the sipho characters in sympatric populations of Aedes caspius (Pallas, 1771) and Aedes dorsalis (Meigen, 1830). Issue 2 (1998) - Milankov, V.; Petric, D.; Vujic, A.; Lj, Lj; Vapa, Vapa; Kerenji, A.
No abstract available